A Catalytic Immune Activator Based on Magnetic Nanoparticles to Reprogram the Immunoecology of Breast Cancer from "Cold" to "Hot" State. Issue 21 (20th September 2022) - Wang, Shuren; Wang, Zhiyi; Li, Ziyuan; Xu, Junjie; Meng, Xiangxi; Zhao, Zijing; Hou, Yanglong
Abstract: Triple‐negative breast cancer (TNBC) as "cold" tumor is characterized by severe immunosuppression of the tumor microenvironment (TME). To effectively activate the immune response of TNBC, a new kind of therapy strategy called cancer catalytic immunotherapy is proposed based on magnetic nanoparticles (NPs) as immune activators. Utilizing the weak acidity and excessive hydrogen peroxide of TME, these magnetic NPs can release ferrous ions to promote Fenton reaction, leading to abundant ·OH and reactive oxygen species (ROS) for ultimately killing cancer cells. Mechanistically, these magnetic NPs activate the ROS‐related signaling pathway to generate more ROS. Meanwhile, these magnetic NPs with unique immunological properties can promote the maturation of dendritic cells and the polarization of macrophages from M2 to M1, resulting in the infiltration of more T cells to reprogram the immunoecology of TNBC from "cold" to "hot" state. Besides directly affecting immune cells, these magnetic NPs can also affect the secretion of some immune‐related cytokines by cancer cells, to further indirectly activate the immune response. In conclusion, these catalytic immune activators are designed to achieve the synergistic treatment of chemodynamic therapy‐enhanced immunotherapy guided by computed tomography (CT)/near‐infrared region‐II (NIR‐II) dual‐mode imaging, providing a new strategy for TNBC treatment. Abstract : These nanoparticles generate reactive oxygen species through activating NF‐ κ B pathway, meanwhile, promote the maturation of dendritic cells and the polarization of macrophages from M2 to M1, resulting in the infiltration of more T cells. These nanoparticles also affect the secretion of some cytokines to further indirectly activate the immune response.